2017
DOI: 10.1111/jam.13570
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the triple-component linoleic acid isomerase inLactobacillus plantarumZS2058 by genetic manipulation

Abstract: Multicomponent linoleic acid isomerase provided important results for illustration unique mechanism for CLA production in Lact. plantarum ZS2058. Lactobacilli with CLA production ability offer novel opportunities for functional food development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 34 publications
2
31
0
Order By: Relevance
“…As discussed above, evidence shows the existence of a multienzymatic complex, and studies have confirmed that at least lactobacilli synthesize CFA through a mechanism that may not involve only LAI (84,90,91): the initial step is the hydration of LA by 10-LAH, resulting in 10-HOE acid that is oxidized by a short-chain hydrogenase/oxidoreductase (DH), which is afterwards transformed into 10-oxotrans-11-octadecenoic acid by the action of an acetoacetate decarboxylase (DC) and reduced by DH (10-hydroxy-trans-11-octadecenoic), while finally, LAH leads to the production of RA and C 18:2 t9, t11 (Fig. 3).…”
Section: Multienzymatic Complexes and Possible Synthesis Pathwaysmentioning
confidence: 82%
See 2 more Smart Citations
“…As discussed above, evidence shows the existence of a multienzymatic complex, and studies have confirmed that at least lactobacilli synthesize CFA through a mechanism that may not involve only LAI (84,90,91): the initial step is the hydration of LA by 10-LAH, resulting in 10-HOE acid that is oxidized by a short-chain hydrogenase/oxidoreductase (DH), which is afterwards transformed into 10-oxotrans-11-octadecenoic acid by the action of an acetoacetate decarboxylase (DC) and reduced by DH (10-hydroxy-trans-11-octadecenoic), while finally, LAH leads to the production of RA and C 18:2 t9, t11 (Fig. 3).…”
Section: Multienzymatic Complexes and Possible Synthesis Pathwaysmentioning
confidence: 82%
“…Moreover, in a subsequent study, the same group confirmed, through a gene deletion mutant, that the multiple-component LAI (MCRA, DH, and DC) was responsible for the L. plantarum ZS2058 CLA-producing capacity (91). The mcra gene deletion mutant failed to produce CLA or any intermediate.…”
Section: Cla Production: the Action Of A Multicomponent System?mentioning
confidence: 82%
See 1 more Smart Citation
“…M206033, China Center for Type Culture Collection) was first cultured in de Man, Rogosa and Sharpe (MRS) medium, which consisted of 1% tryptone, 1% meat extract, 0·5% yeast extract, 2% glucose, 0·1% Tween 80, 0·2% K 2 HPO 4 , 0·5% sodium acetate, 0·2% diammonium citrate, 0·02% MgSO 4 ·7H 2 O and 0·005% MnSO 4 ·H 2 O (pH 6·5) at 37°C in an anaerobic atmosphere (10% H 2 , 10% CO 2 , and 80% N 2 ) in a anaerobic workstation (AW400TG; Electrotek Scientific Ltd, West Yorkshire, UK). Six genetically modified strains of L. plantarum ZS2058 (Yang et al ), including ZS2058Δ mcra , ZS2058Δ mcra /pNZ44‐ mcra , ZS2058Δ dh , ZS2058Δ dh /pNZ44‐ dh , ZS2058Δ dc and ZS2058Δ dc /pNZ44‐ dc, were cultured in MRS medium as the wild type. Escherichia coli BL21 (DE3) carrying the plasmid pET28a harbouring mcra , dh and dc from L. plantarum ZS2058, respectively, were routinely cultured aerobically in Luria–Bertani (LB) medium (1% tryptone, 0·5% yeast extract, 1% NaCl) at 37°C in the presence of kanamycin (10 μg ml −1 ) as a selective marker.…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, Liavonchanka et al () found that PAI could convert different fatty acids to their conjugated fatty acids, including CLA and CLNA, indicating CLA and CLNA production might share the same enzyme(s) in some bacteria. In our previous study, linoleate isomerase complex for CLA production in L. plantarum ZS2058 was identified via overexpression (Yang et al ) and knockout mutation (Yang et al ). In the current work, the genetic determinates for CLNA generation will be further investigated for L. plantarum ZS2058.…”
Section: Introductionmentioning
confidence: 99%